1999
DOI: 10.1038/sj.bjc.6690753
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein expression correlates with metastatic and proliferative potential in squamous cell carcinoma of the oesophagus

Abstract: Squamous cell carcinoma (SCC) of the oesophagus is well recognized for its aggressive biological behaviour, in respect of local infiltration and metastases to regional lymph nodes and distant organs (Orrigner, 1997). Extra-oesophageal tumour spread is present in 70% of cases at the time of diagnosis, and the 5-year survival is only 3% when lymph node metastases are present, compared with 42% in lymph node negative patients (Orrigner, 1997). Patients with distant metastasis also have a poor prognosis, with a 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
4
40
1
3
Order By: Relevance
“…We confirmed that this approach is equivalent to the traditional risk factor method, which typically requires a comprehensive set of clinical data. The biological significance of the epigenetic approach is supported by studies investigating the pathogenesis of SCC, which find that HOXA9 protein expression is deregulated in SCC (32), that oncogenesis is triggered by silencing NEFH to activate the Akt/b-catenin pathway (33), that the prognosis of SCC is worsened by hypermethylating UCHL1 (34) that interacts with p53 through the deubiquitination pathway (35), and that overexpressing MT is associated with metastatic and proliferative activity (36). None of these 4 genes had previously been correlated with carcinogen exposure or with cancer risk prediction.…”
Section: Discussionmentioning
confidence: 94%
“…We confirmed that this approach is equivalent to the traditional risk factor method, which typically requires a comprehensive set of clinical data. The biological significance of the epigenetic approach is supported by studies investigating the pathogenesis of SCC, which find that HOXA9 protein expression is deregulated in SCC (32), that oncogenesis is triggered by silencing NEFH to activate the Akt/b-catenin pathway (33), that the prognosis of SCC is worsened by hypermethylating UCHL1 (34) that interacts with p53 through the deubiquitination pathway (35), and that overexpressing MT is associated with metastatic and proliferative activity (36). None of these 4 genes had previously been correlated with carcinogen exposure or with cancer risk prediction.…”
Section: Discussionmentioning
confidence: 94%
“…These KGF and KGFR oligo-DNAs were haptenized by introducing T-T dimers by 12 000 J/m 2 ultraviolet irradiation, as described previously. 36,37 We performed preliminary immunodetection and dot-blot hybridization using KGF and KGFR probes as detailed previously, 37,38 and these results indicated that antisense probes were specific and had adequate sensitivity to be useful for in situ hybridization.…”
Section: Probes and Labelingmentioning
confidence: 99%
“…To estimate the amount of RNA retained in the paraffin sections, methyl green-pyronin Y staining was performed before in situ hybridization (ISH), according to Shutle et al (1992). ISH was performed using digoxigenin-labeled oligonucleotide probes as previously described (Koji and Brenner 1993;Hishikawa et al 1999). Briefly, the sections were warmed at 60°C for 30 min, deparaffinized with toluene and rehydrated through decreasing concentrations of ethanol.…”
Section: In Situ Hybridizationmentioning
confidence: 99%